Use of electromagnetic radiation from fractures for mining-induced stress field assessment. (13th April 2018) - Song, Dazhao; Wang, Enyuan; He, Xueqiu; Jia, Haishan; Qiu, Liming; Chen, Peng; Wang, Sida
Abstract: This paper presents an electromagnetic radiation-based method to qualitatively assess mine-induced stress field at the longwall face. We first analyze the correlation between electromagnetic (EM) signals and stress, and then measure the signals and drilling bits in both the strike and dip directions at the 11702 working face of Nuodong Coal Mine, China, which indirectly verifies this method. Results show that there is a positive correlation between EM intensity and stress. In the same coal seam, the frequency of EM signals is inversely proportional to the extended size of the cracks inside the coal rock, and the dominant frequency (DF) of the EM signal is negatively related to external stress. Test results in Nuodong Coal Mine show that the EM intensity and DF can well reflect a stress relief zone, concentration zone and original zone. In addition, through field test and theoretical calculation, we can ascertain that the crack propagation length is from several centimeters to greater than 20 cm. The stress magnitude inside the coal rock can be qualitatively evaluated by using the correlation of the EM signal intensity, frequency and stress.